THE INFLUENCE OF ANTAGONISTIC BACTERIA SERRATIA PLYMUTHICA AND BACILLUS SUBTILIS ON AFFECTION OF SALAD PLANTS BY RHIZOCTONIA SOLANI - V. D. Migunova; N. F. Ryabchenko (Российский паразитологический журнал, 2016)
High efficiency of mixture of two bacterial strains Serratia plymuthica and Bacillus  subtilis was shown against development of Rhizoctonia solani on plants of salad variety Leny  (Nunhems). Survival, biomass of plants, and number  of affected plants and leaves were analyzed in the experiment. Efficiency of application of a preparation of mixture bacterial strains was comparable with the chemical preparation Monceren L recommended for suppression of this disease caused Rhizoctonia solani.